Speedy responses: Effects of higher benefits on take-up and division of parental leave - Ylva Moberg (Uppsala University, Department of Economics, 2018)
Using population wide register data, I exploit the "speed premium" rule in the Swedish parental leave system to estimate the causal effect of a change in the level of benefits per day on the utilization of parental leave. The results show that a 1% (5 SEK ≈ 0.54) increase in the mother's benefit level per day increases her length of leave by 2.6 days (≈ 1%). Fathers respond by reducing their own time on leave by 1.9 days, i.e. about 75% of the mother's increase. This suggests that changes in the benefit level effects not only the recipient's time on leave, but also the division of leave between parents. This is the first paper to causally estimate the elasticity of take-up duration (length of spell) with respect to the parental leave benefit level; which is found to be equal to 1 for mothers.
urn:nbn:se:uu:diva-366299
Keywords: D13; J13; J16; J22; 330; parental leave; division of labor; labor supply; take-up elasticity